Diversity of cultivable lactic acid bacteria and bacilli in traditional fermented foods in Vietnam - Giang Phan Thi Hang; Markéta Husáková; Petr Kaštánek; Petra Patakova (Czech Journal of Food Sciences)
Lactic acid bacteria (LAB) are commonly used in many European and Asian traditional fermented foods such as yogurt, cheese, sourdough, meat, fruit, vegetables, cereal products, sour spring rolls, fish sauce, sour shrimp, chao, ruou nep, tofu. They not only improve the flavour and texture of fermented products but also they inhibit the development of spoilage bacteria as antimicrobial agents. In this study, thirty-five traditional Vietnamese fermented products were collected for isolation, identification, and characterisation of LAB and bacilli. There were fifty-three species of LAB isolated from samples such as Lactococcus lactis, Lactiplantibacillus plantarum, Limosilactobacillus fermentum, Liquorilactobacillus nagelli, Companilactobacillus farciminis, Levilactobacillus brevis, Lactiplantibacillus pentosus, Lactococcus garvieae, Lactilactobacillus sakei, and twenty-one species of bacilli such as Priestia megaterium, Bacillus cereus, Bacillus pumilus, Metabacillus indicus. This study aimed to provide information about the occurrence of LAB and bacilli in traditional fermented foods in Vietnam and their brief characterisation.